The effect of water related traps on the reliability of organic based transistors - Gomes, Henrique L. (2015)
The electrical stability of metal-insulator semiconductor (MIS) capacitors and field-effect transistor structures based in organic semiconductors were investigated. The device characteristics were studied using steady state measurements AC admittance measurements as well as techniques for addressing trap states. Temperature-dependent measurements show clear evidence that an electrical instability occurs above 200 K and is caused by an electronic trapping process. Experimental results show that water is responsible for the trapping mechanism. (c) 2006 Elsevier B.V. All rights reserved.